2008
DOI: 10.1158/1535-7163.mct-07-0457
|View full text |Cite
|
Sign up to set email alerts
|

Dicoumarol down-regulates human PTTG1/Securin mRNA expression through inhibition of Hsp90

Abstract: Securin, the natural inhibitor of sister chromatid untimely separation, is a protooncogene overexpressed in tumors.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…On the other hand, it can mean the induction of further aneuploidy, as a side effect. Recently, we have described that dicoumarol is an unsuspected Hsp90 inhibitor (Hernandez et al, 2008). Also, we showed that treatment of cancer cells with dicoumarol and other Hsp90 inhibitors reduces the levels of securin through repression of its gene.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…On the other hand, it can mean the induction of further aneuploidy, as a side effect. Recently, we have described that dicoumarol is an unsuspected Hsp90 inhibitor (Hernandez et al, 2008). Also, we showed that treatment of cancer cells with dicoumarol and other Hsp90 inhibitors reduces the levels of securin through repression of its gene.…”
Section: Introductionmentioning
confidence: 95%
“…Floating and adherent cells were stained with propidium iodide and processed for flow cytometry analysis on a Coulter Epics XL apparatus as described (Hernandez et al, 2008). Determination of aneuploidy in cultured cells was estimated according to Muehlbauer and Schuler (2005).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Heat shock protein 90 (Hsp90) is an essential molecular chaperone involved in the folding and stabilization of client proteins which regulate the survival of cancer cells. Hsp90 inhibitors have been reported to repress PTTG1 expression in carcinoma cells [10,11], and are thought to act in a similar way in pituitary tumor cells. Previous studies have demonstrated that Hsp90 inhibitors decreased POMC mRNA and ACTH levels in AtT-20 cells [12,13].…”
mentioning
confidence: 99%
“…Earlier studies have used a similar approach using a cell-based system to monitor the Hsp90 protein folding machinery; however, that approach utilized aliquots of cell extracts to examine Hsp90 inhibition, which is not amenable to HTS. 34,35 Furthermore, lysing of the cells to prepare the cell extract has the potential to physically disrupt the Hsp90 heteroprotein complexes, leading to a loss of physiological relevance. In contrast, this approach is novel, as Hsp90 inhibition can be measured in intact cancer cells without disruption of the native complexes.…”
Section: Discussionmentioning
confidence: 99%